Evaluation the Influences of Using Waste Brick Powder on the Geotechnical Characteristics of Sulaimani Governorate, Northern Iraq Fine-Grained Soil - Qadir, Sangar J.; Rafiq, Dr.Serwan Kh.; Muhedin, Daban Abdulthahir (Sulaimani Journal for Engineering Sciences, 2024)
Expansive soils are a significant challenge in geotechnical engineering due to their volume-changing behavior in response to moisture fluctuation. The aim of this study is to evaluate the influence of waste brick powder (WBP) on certain geotechnical characteristics of clayey soil (CL soil) collected from the Sulaymaniyah Governorate, North of Iraq. Waste brick powder was incorporated at proportions of 0%, 5%, 10%, 15%, 20%, 25%, and 30%, replacing an equivalent dry mass of the natural soil sample. Consistency properties, linear shrinkage limit (LSL), unconfined compressive strength (UCS), standard Proctor test, and compressibility properties were assessed for both untreated and WBP-treated soil samples. The results showed a remarkable decrease in the values of liquid limit (LL), plasticity index (PI), and LSL by 22%, 56%, and 57%, respectively. Additionally, the compression index (Cc), recompression index (Cr), and optimum moisture content (OMC) experienced reductions of 46%, 44%, and 14%, respectively. The UCS increased significantly from 411.2 kN/m² to 679.6 kN/m² with the addition of 30% WBP. These outcomes confirm that incorporating up to 30% WBP notably enhances the strength of fine-grained soils and mitigates the environmental hazards associated with this type of waste.
Keywords: Expansive soil; Geotechnical characteristics; Waste brick powder; Unconfined compressive strength; Compressibility properties